Distribution and analysis of suspected measles and rubella cases in Bangladesh - Nowshin, Sazia; Rehana, Jinat; Salam, Sabia; Ahsan, Shamima; Jahan, Sarder Mohammad Shahriar (International Journal of Research in Medical Sciences, 2026)
Background: Measles and rubella remain significant public health concerns in the WHO Southeast Asia Region. Strengthening surveillance through technology-based systems in Bangladesh aims to enhance data accuracy, reporting efficiency, and timely response for effective disease control. Methods: This retrospective cross-sectional study analyzed from January 2023 to December 2023 national surveillance data on suspected measles and rubella cases from all eight divisions of Bangladesh. Demographic, laboratory, and epidemiological data were extracted from the DGHS system. Serological testing (IgM ELISA) and PCR confirmation followed WHO protocols. Data were cleaned and analyzed using descriptive and correlation statistics to assess case distribution, confirmation rates, and regional variations. Results: In 2023, Bangladesh reported 7,061 suspected measles cases, with the highest in Dhaka and Chittagong divisions. Of 6,309 samples tested, 3.4% were measles IgM positive and 2,295 rubella IgM positive, predominantly among children aged 5–14 years. Co-infection occurred in 13 cases. Confirmed measles and rubella incidences were 1.45 and 0.99 per million, respectively. Laboratories reported 98% of results within 4 days, and 98% of investigations were initiated within 48 hours, reflecting strong surveillance and response performance. Conclusions: This study highlights the distribution and epidemiological trends of suspected measles and rubella cases across Bangladesh. The findings underscore ongoing transmission in certain regions and emphasize the need for strengthened surveillance, timely laboratory confirmation, and improved vaccination coverage to achieve and sustain measles and rubella elimination goals nationwide.